New science of learning : exploration in mind, brain, and education - Saleh, Issa M.; Khine, Myint Swe (Brill, 2023)
"In an attempt to foster effective learning for the students, educators and researchers have been examining the complex relations between psychological, biological, sociological, and cultural aspects of the educative process. The common goal is to promote deep learning and maximize the potential of next-generation students in constructing knowledge, understanding, supporting, and advancing skills in their chosen fields. In the past decades, scientists and educational researchers are developing a new understanding of how the brain works and gaining knowledge of brain research that can transform how they teach in class. Recent discoveries in non-invasive brain imaging and cognitive neuroscience are providing fresh perspectives and mechanisms of learning. The chapters in this book will portray theoretical frameworks, thought-provoking ideas, and promising efforts in framing new science of learning"-- Provided by publisher.
Keywords: Learning, Psychology of.; Cognitive science.; Cognition in children.; Teaching.; Education -- Aims and objectives.; Psychologie de l'apprentissage.; Sciences cognitives.; Cognition chez l'enfant.; Cognition in children; Cognitive science; Education -- Aims and objectives; Learning, Psychology of; Teaching